Cell Separation in Aqueous Two‐Phase Systems − Influence of Polymer Molecular Weight and Tie‐Line Length on the Resolution of Five Model Cell Lines. Issue 2 (22nd November 2017) - Zimmermann, Sarah; Gretzinger, Sarah; Zimmermann, Philipp K.; Bogsnes, Are; Hansson, Mattias; Hubbuch, Jürgen
Abstract : The availability of clinical‐scale downstream processing strategies for cell‐based products presents a critical juncture between basic research and clinical development. Aqueous two‐phase systems (ATPS) facilitate the label‐free, scalable, and cost‐effective separation of cells, and are a versatile tool for downstream processing of cell‐based therapeutics. Here, we report the application of a previously developed robotic screening platform, here extended to enable a multiplexed high‐throughput cell partitioning analysis in ATPS. We investigated the influence of polymer molecular weight and tie‐line length on the resolution of five model cell lines in "charge‐sensitive" polyethylene‐glycol (PEG)‐dextran ATPS. We show, how these factors influence cell partitioning, and that the combination of low molecular weight PEGs and high molecular weight dextrans enable the highest resolution of the five cell lines. Furthermore, we demonstrate that the separability of each cell line from the mixture is highly dependent on the polymer molecular weight composition and tie‐line length. Using a countercurrent distribution model we demonstrate that our screenings yielded conditions that theoretically enable the isolation of four of the five cell lines with high purity (>99.9%) and yield. Abstract : Aqueous two‐phase systems (ATPS) have been a useful tool in downstream processing for cell‐based products, since they facilitate label‐free, scalable, and cost‐effective separation of cells. Here, the authors report the extension of the previously developed high‐throughput screening (HTS) platform by a cell barcoding procedure, to enable multiplexed cell partitioning analysis. Further, a case study demonstrated the influence of polymer molecular weight and tie‐line length on the resolution of five model cell lines using a countercurrent distribution model.